PENDIDIKAN BERBASIS ADIL GENDER (Membongkar Akar Permasalahan dan Pengarusutamaan Gender sebagai Sebuah Solusi) - MARDIA, MARDIA (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Responsive gender education is a foundation of women?s empowerment. It is conducted not to create a higher statue for women. In the contrary, it is held to improve the independency, power and participation of women in order to avoid discrimination often happened to them. Therefore, a co-operative work by government, the private (non- government) institutions, independent institutions, and stakeholders of gender issue is expected to produce better public adjustments of gender. The gender mainstream will not only encourage to a stabilized and adjusted gender, but also will hold the government accountability of public to be in increase.